2017
DOI: 10.1371/journal.pone.0179690
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder and other mental disorders in the general population after Lorca’s earthquakes, 2011 (Murcia, Spain): A cross-sectional study

Abstract: AimsTo describe the prevalence and severity of mental disorders and to examine differences in risk among those with and without a lifetime history prior to a moderate magnitude earthquake that took place in Lorca (Murcia, Spain) at roughly the mid-point (on May 11, 2011) of the time interval in which a regional epidemiological survey was already being carried out (June 2010 –May 2012).MethodsThe PEGASUS-Murcia project is a cross-sectional face-to-face interview survey of a representative sample of non-institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…While no differences in MDD were observed between males and females, a surprisingly high proportion of females-19.8% and 16.5%-met criteria for PD and GAD, respectively. This is generally in line with the study by Navarro-Mateu et al (2017), who reported higher prevalence rates for women; nevertheless, the prevalence rate in our study obtained by screening tools was generally higher. We also found that young adults (ages 18-25 years) and middle-age adults (ages 26-39 years) presented more emotional disorders (GAD, MDD, and PD) than older people.…”
Section: Discussionsupporting
confidence: 93%
“…While no differences in MDD were observed between males and females, a surprisingly high proportion of females-19.8% and 16.5%-met criteria for PD and GAD, respectively. This is generally in line with the study by Navarro-Mateu et al (2017), who reported higher prevalence rates for women; nevertheless, the prevalence rate in our study obtained by screening tools was generally higher. We also found that young adults (ages 18-25 years) and middle-age adults (ages 26-39 years) presented more emotional disorders (GAD, MDD, and PD) than older people.…”
Section: Discussionsupporting
confidence: 93%
“…Those authors argued that the increase of prevalence was due to stressors such as socioeconomic risks. Other studies have shown that the prevalence of emotional disorders rises in response to natural disasters (earthquakes) (26) and terrorist attacks (8). Then, the psychological impact of the global pandemic likely could explain the large increase in diagnoses of emotional disorders observed in our study (27).…”
Section: Resultsmentioning
confidence: 99%
“…Early implementation of mental care with specific therapeutic interventions will reduce subsequent posttraumatic stress disorders in survivors. 37 Public health professionals will collect the necessary (epidemiological) data about morbidity and mor-Earthquakes and their impacts Artículo originAl tality (types and incidence); needs for shelters, water, food, drugs; and will be the most precious educators, at the disaster scene, related to health and survival. Based on collected data, organization of help will be much more concrete, thorough and faster; and, with the agreement of medical professionals, will offer uniform information to the affected population: where to go, how to act, who and when should seek immediate help, how to protect yourself and the closest ones.…”
Section: Public Health Impactsmentioning
confidence: 99%